A carbon / vanadium nitride / manganese oxide composite material and its preparation method and application

By preparing carbon/vanaphthalide/manganese oxide composite materials, using high-temperature pyrolysis and hydrothermal reaction technology, the problem of low energy density of existing electrode materials has been solved, and the high specific capacitance and energy density has been improved, which is suitable for supercapacitors Electrode material.

CN118866562BActive Publication Date: 2025-01-03NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411208311.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-03
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The low energy density of existing supercapacitor electrode materials limits its further development in practical applications, especially because the specific capacity of binary composite materials is low, making it difficult to effectively improve the energy density.

Method used

Using carbon/vanavale nitride/manganese oxide composite materials, the secondary pyrolysis preparation is carried out through the pyrolysis, acidification treatment and hydrothermal reaction of carbon nitride precursor, combined with uniform stirring of vanadium pentoxide sol and manganese source, to produce high-quality Carbon/vanadiode/manganese oxide composite with specific capacitance and energy density.

Benefits of technology

The specific capacitance and energy density of the composite material are improved, with the maximum specific capacitance reaching 424F/g, and the electrode material performance and stability of the supercapacitor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118866562B_ABST
    Figure CN118866562B_ABST
Patent Text Reader

Abstract

The invention discloses a carbon / vanadium nitride / manganese oxide composite material and its preparation method and application, belonging to the technical field of electrode materials. The preparation method of the carbon / vanadium nitride / manganese oxide composite material comprises the following steps: a carbon nitride precursor is subjected to a primary pyrolysis at 550°C to 600°C to obtain carbon nitride; the carbon nitride is subjected to an acid treatment to obtain protonated carbon nitride; a manganese source is added to a vanadium pentoxide sol solution and stirred evenly, and then a hydrothermal reaction is carried out at 180°C to 200°C to obtain a manganese-vanadium composite; under a protective atmosphere, the manganese-vanadium composite and the protonated carbon nitride are subjected to a secondary pyrolysis at 600°C to 900°C to obtain a carbon / vanadium nitride / manganese oxide composite. The carbon / vanadium nitride / manganese oxide composite prepared by the invention has high specific capacitance and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and more specifically to a carbon / vanadium nitride / manganese oxide composite material and a preparation method and application thereof. Background Art

[0002] Electrochemical capacitors are also called supercapacitors or ultra-large capacity capacitors. Compared with traditional capacitors (capacitance in the range of microfarads and millifarads), supercapacitors use high specific surface area carbon materials to form a double layer charge storage on the surface. In addition, electrode materials such as metal oxides or nitrides can be used to store charges by surface oxidation reactions. A single supercapacitor can store higher rated capacity, up to tens, hundreds or even thousands of farads; compared with the battery cycle life of <1500 times, supercapacitors have a cycle life of tens of thousands and millions of times. Its excellent charge and discharge life, high power density, and environmental friendliness have led to more extensive applications and research. Among them, common application areas of supercapacitors include: consumer electronics, backup power supplies, renewable energy power generation systems, rail transportation, military equipment, aerospace, etc. However, the relatively low energy density limits the further development of its practical application.

[0003] The main methods to improve its energy density are to increase the specific capacitance of the electrode material and expand its potential window. Nitrides, especially vanadium nitride, have received widespread attention due to their wide potential window (-1.2V~0V) and high specific capacitance. Inventor Tan Yongtao et al. published an article titled "Construction of Mo2N nanoparticles embedded inN,O-doped carbon sheets and its supercapacitive behaviors" in the Journal of Alloys and Compounds, preparing a binary composite material, but the specific capacity of the binary composite material is still low, which limits the improvement of its energy density. Summary of the invention

[0004] In view of the above problems, the present invention provides a carbon / vanadium nitride / manganese oxide composite material and a preparation method and application thereof. The carbon / vanadium nitride / manganese oxide composite material prepared by the present invention has high specific capacitance and energy density.

[0005] The first object of the present invention is to provide a method for preparing a carbon / vanadium nitride / manganese oxide composite material, comprising the following steps:

[0006] The carbon nitride precursor is pyrolyzed once at 550°C to 600°C to obtain carbon nitride; for example, the temperature of the pyrolysis is 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0007] acidifying the carbon nitride to obtain protonated carbon nitride;

[0008] After adding a manganese source to the vanadium pentoxide sol solution and stirring evenly, a hydrothermal reaction is carried out at 180°C to 200°C to obtain a manganese-vanadium complex; the temperature of the hydrothermal reaction is 180°C, 190°C, 200°C, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0009] Under a protective atmosphere, the manganese-vanadium complex and protonated carbon nitride are subjected to secondary pyrolysis at 600° C. to 900° C. to obtain a carbon / vanadium nitride / manganese oxide complex. For example, the temperature of the secondary pyrolysis is 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0010] In a preferred embodiment of the present invention, the ratio of vanadium pentoxide to manganese source in the vanadium pentoxide sol solution is 2mmol:0.2g-4g. For example, the ratio of vanadium pentoxide to manganese source in the vanadium pentoxide sol solution is 2mmol:0.2g, 2mmol:0.5g, 2mmol:1g, 2mmol:1.5g, 2mmol:2g, 2mmol:2.5g, 2mmol:3g, 2mmol:3.5g, 2mmol:4g, etc., but is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0011] In a preferred embodiment of the present invention, the reaction time of the hydrothermal reaction is 1 h to 12 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0012] In a preferred embodiment of the present invention, the mass ratio of the manganese vanadium complex and the protonated carbon nitride is 1:3 to 20. For example, the mass ratio of the manganese vanadium complex and the protonated carbon nitride is 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0013] In a preferred embodiment of the present invention, the time for secondary pyrolysis is 1 h to 4 h, for example, the time for secondary pyrolysis is 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0014] In a preferred embodiment of the present invention, the acidification treatment is to add carbon nitride to hydrochloric acid and react at room temperature for 2h to 5h, for example, the reaction time is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, the ratio of carbon nitride to hydrochloric acid is 1g:25-30ml, for example, the ratio of carbon nitride to hydrochloric acid is 1g:25ml, 1g:26ml, 1g:27ml, 1g:28ml, 1g:29ml, 1g:30ml, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the time for a pyrolysis is 1 h to 3 h, for example, the time for a pyrolysis is 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0017] The second object of the present invention is to provide a carbon / vanadium nitride / manganese oxide composite material prepared by the above preparation method.

[0018] The third object of the present invention is to provide the use of the above carbon / vanadium nitride / manganese oxide composite material in the preparation of electrode materials.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention utilizes pyrolysis of metal compound precursors at high temperature to obtain C3N4, and mixes and sinters the protonated C3N4 with the prepared manganese vanadium oxide to obtain a ternary composite. During the sintering process, the CN bond of C3N4 breaks, self-sacrifices to generate carbon material, and provides a N source. In addition, the MnVO composite also breaks the Mn-V bond, the VO bond breaks, the NV bond is reconstructed at high temperature to produce VN, and VO is reduced to VN by carbon; the Mn-O bond is reconstructed, and finally a carbon / vanadium nitride / manganese oxide composite material is obtained. The composite material prepared by this method is applied to the electrode material of supercapacitors, and C, VN and MnOx work synergistically, thereby effectively improving the specific capacitance and stability of the composite material, and its highest specific capacitance is 424F / g. In addition, the energy density of the device is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Figures 1 and 2 are scanning electron microscope images, transmission images and element distribution images of different samples, wherein Figure a is a scanning electron microscope image of the composite material prepared in Comparative Example 1; Figure b is a scanning electron microscope image of the composite material prepared in Comparative Example 2, Figure c is a scanning electron microscope image of the composite material prepared in Example 1, Figure d is a scanning electron microscope image of the composite material prepared in Example 2, Figure e is a scanning electron microscope image of the composite material prepared in Example 3, Figure f is a scanning electron microscope image of the composite material prepared in Example 4, Figure g is a scanning electron microscope image of the composite material prepared in Example 4, h is a transmission image of the composite material prepared in Example 3 with a scale of 20 nm, the inset in Figure h is a particle size distribution image of the composite material prepared in Example 3, i is a high-magnification transmission image of the composite material prepared in Example 3 with a scale of 20 nm, the inset in Figure i is a local enlarged image of Figure i, and j is an element distribution image of the composite material prepared in Example 3.

[0022] Figure 2 XRD patterns of different samples.

[0023] Figure 3 Figure 2 is the electrochemical properties of the composite materials at different Mn contents, where a is the cyclic voltammetry curve, b is the constant current charge and discharge curve, c is the specific capacitance curve, and the inset in Figure c is the specific capacitance bar graph.

[0024] Figure 4 The AC impedance curve of the composite material with different Mn contents, where the inset is Figure 4 A partial enlarged view of .

[0025] Figure 5 Shows the electrochemical properties of the composite material at different temperatures, where a is the cyclic voltammetry curve, b is the constant current charge-discharge curve, and c is the specific capacitance curve.

[0026] Figure 6 The AC impedance curves of the composite materials at different temperatures, where the illustration is Figure 6 A partial enlarged view of . DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] As described in the background art, the existing composite materials have low specific capacity, which limits the improvement of their energy density. Therefore, the present invention prepares a multi-component composite heterojunction material, namely carbon / vanadium nitride / manganese oxide (C / VN / MnO x) The composite material helps to improve the specific capacitance of the composite material and the energy density during the process. The specific technical solution is as follows:

[0029] A method for preparing a carbon / vanadium nitride / manganese oxide composite material comprises the following steps:

[0030] The carbon nitride precursor is pyrolyzed once at 550°C to 600°C to obtain carbon nitride;

[0031] acidifying the carbon nitride to obtain protonated carbon nitride;

[0032] A manganese source is added to the vanadium pentoxide sol solution and stirred evenly, and then a hydrothermal reaction is carried out at 180° C. to 200° C. to obtain a manganese-vanadium complex;

[0033] Under a protective atmosphere, the manganese-vanadium complex and protonated carbon nitride are subjected to secondary pyrolysis at 600° C. to 900° C. to obtain a carbon / vanadium nitride / manganese oxide complex.

[0034] The present invention is to decompose the carbon nitride precursor in a muffle furnace to prepare C3N4, and then place it in hydrochloric acid for protonation so that its surface has a positive charge. In addition, MnSO4 is added to the vanadium pentoxide sol solution. At this time, the solution is reddish brown and acidic. It is transferred to a 100mL reactor for hydrothermal reaction to obtain a composite of Mn-doped vanadium oxide and manganese vanadate. Finally, the protonated C3N4 is mixed with the prepared manganese vanadium oxide for sintering. During the sintering process, the CN bond of C3N4 breaks to generate carbon material and provide a N source. In addition, the MnVO composite also breaks the Mn-V bond, the VO bond breaks, the NV bond is reconstructed at high temperature to produce VN, and the VO bond is reduced to VN by carbon; the Mn-O bond is reconstructed, and finally a C / VN / MnO composite material is obtained. The composite material prepared by this method is applied to the electrode material of the supercapacitor, and its highest specific capacitance is 424F / g, which effectively improves the specific capacitance and stability of the composite material, and also improves the energy density of the device.

[0035] The carbon nitride precursor used in the present invention is urea, melamine or dicyandiamide.

[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercial products, and their specifications are conventional specifications in the art. The concentration of concentrated hydrochloric acid used in the present invention is 36% to 38%.

[0037] Example 1

[0038] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0039] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0040] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 0.2 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0041] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 700°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -700-0.2.

[0042] Example 2

[0043] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0044] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0045] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 0.5 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0046] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 700°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -700-0.5.

[0047] Example 3

[0048] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0049] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0050] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0051] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 700°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -700-1.

[0052] Example 4

[0053] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0054] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0055] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 2 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0056] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 700°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -700-2.

[0057] Example 5

[0058] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0059] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0060] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 4 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0061] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 700°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -700-4.

[0062] Example 6

[0063] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0064] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0065] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0066] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 600°C for 2h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -600-1.

[0067] Example 7

[0068] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0069] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0070] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0071] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 800°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -800-1.

[0072] Example 8

[0073] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0074] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0075] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 4 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0076] Step 4: Mix the manganese-vanadium complex with protonated C3N4 in a mass ratio of 1:10, and pyrolyze at 900°C for 2 h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material, denoted as C / VN / MnO x -900-1.

[0077] Example 9

[0078] Step 1: 10 g of melamine is pyrolyzed in air at 600° C. for 1 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0079] Step 2: 1 g of C3N4 was placed in 30 mL of concentrated hydrochloric acid solution, stirred for 5 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0080] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 200 ° C for 5 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0081] Step 4: Mix the manganese-vanadium complex and protonated C3N4 in a mass ratio of 1:10, and perform high-temperature pyrolysis at 800°C for 3 hours in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material.

[0082] Example 10

[0083] Step 1: 10 g of melamine is pyrolyzed in air at 580° C. for 3 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0084] Step 2: 1 g of C3N4 was placed in 28 mL of concentrated hydrochloric acid solution, stirred for 2 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0085] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 190 ° C for 1 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0086] Step 4: Mix the manganese-vanadium complex and protonated C3N4 in a mass ratio of 1:10, and perform high-temperature pyrolysis at 900°C for 1 hour in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material.

[0087] Embodiment 11

[0088] Step 1: 10 g of melamine is pyrolyzed in air at 600° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0089] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0090] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. 1 g of manganese sulfate was added and stirred for 15 min until it became clear. Then, the solution was hydrothermally reacted at 180 ° C for 12 h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex.

[0091] Step 4: Mix the manganese-vanadium complex and protonated C3N4 in a mass ratio of 1:10, and perform high-temperature pyrolysis at 700°C for 2h in a nitrogen atmosphere to prepare a carbon / vanadium nitride / manganese oxide composite material.

[0092] Comparative Example 1

[0093] Step 1: 10 g of melamine is pyrolyzed in air at 550° C. for 2 h with a muffle furnace heating rate of 2.3° C. / min to obtain C3N4.

[0094] Step 2: 1 g of C3N4 was placed in 25 mL of concentrated hydrochloric acid solution, stirred for 4 h, centrifuged at 8000 rpm, washed and dried at 60° C. to obtain protonated C3N4.

[0095] Step 3: 2 mmol of V2O5 was dispersed in 60 mL of water, and 5 mL of H2O2 was added dropwise and stirred for 30 min until the solution turned into a clear orange-red color. Then, the solution was hydrothermally reacted at 180°C for 4 h, and then cooled to room temperature for washing and drying to obtain a vanadium oxide complex.

[0096] Step 4: Mix the vanadium oxide complex and protonated C3N4 in a mass ratio of 1:10, and perform high-temperature pyrolysis at 700°C for 2h in a nitrogen atmosphere to prepare a carbon / vanadium nitride composite material, which is recorded as C-VN-700.

[0097] Comparative Example 2

[0098] 2mmol of V2O5 was dispersed in 60mL of water, and 5mL of H2O2 was added dropwise and stirred for 30min until the solution turned into a clear orange-red color. 1g of manganese sulfate was added and stirred for 15min until it became clear. Then, the solution was hydrothermally reacted at 180℃ for 4h, and then cooled to room temperature for washing and drying to obtain a manganese-vanadium complex, which was recorded as MnVO.

[0099] Figure 1 Scanning images, transmission images, and element distribution images of different samples. Figure 1 Figure a is a scanning electron microscope photograph of C / VN-700-1 prepared in Comparative Example 1. This sample is a sample without adding Mn source. After the hydrothermal reaction, the vanadium oxide is freeze-dried and sintered with protonated C3N4. The scanning electron microscope shows a flaky structure.

[0100] Figure 1 Figure b shows MnVO prepared after hydrothermal reaction with the addition of Mn source. It is a precursor material, and its scanning electron microscope photo shows an intertwined sheet structure. Figure 1 Figures c-g show C / VN-MnO prepared by sintering MnVO with different Mn additions and protonated C3N4. xThe SEM image of the sample shows a flake structure of accumulated particles. Figure 1 The transmission electron microscope of the h-image also shows that the overall structure is a sheet, and its surface is covered with particles. The particle size distribution is 1-10nm. In addition, the outer layer of the nanoparticles is a carbon layer with a wide thickness distribution of 2-6nm. Figure 1 The 0.206 nm marked in the high-magnification transmission image of the i-image belongs to the interplanar spacing of the (200) crystal plane of VN. Figure 1 The j graph shows that V, N,

[0101] Mn, O and C elements are distributed relatively evenly.

[0102] Figure 2 The XRD diagrams of different samples show that with the increase of Mn content, MnO and MnO2 phases appear. When the addition amount is small, due to the low Mn content, its phase is not detected. Other obvious peaks are attributed to the VN phase.

[0103] Table 1 Element contents tested by XPS

[0104] sample N(at%) V(at%) Mn(at%) C (at%) C / VN-700 15.33 9.06 / 63.84 <![CDATA[C / VN / MnO x -700-0.2]]> 11.53 8.12 0.83 65.29 <![CDATA[C / VN / MnO x -700-0.5]]> 12.35 7.62 1.18 65.62 <![CDATA[C / VN / MnO x -700-1]]> 10.94 5.95 1.78 70.84 <![CDATA[C / VN / MnO x -700-2]]> 10.42 7.35 2.17 67.15 <![CDATA[C / VN / MnO x -700-4]]> 9.44 7.51 2.08 65.89

[0105] However, as shown in Table 1, it can be seen from the XPS test that the actual content of Mn is 0.83 at % to 2.08 at %, indicating that Mn can be successfully introduced according to the preparation method of the present invention.

[0106] Figure 3 The electrochemical performance diagram of samples with different Mn contents is shown in Figure 2. Figure 3 Figure a is the cyclic voltammetry curve of the sample, which has obvious redox peaks. Figure 3 Figure b is the charge and discharge curve, which has a small platform, indicating that they are all pseudocapacitive electrode materials. Figure 3 Figure c is the specific capacitance diagram. At 0.5A / g, C / VN-700, C / VN / MnO x -700-0.2, C / VN / MnO x -700-0.5, C / VN / MnO x -700-1, C / VN / MnO x -700-2 and C / VN / MnO xThe specific capacitances of -700-4 are 150F / g, 323.9F / g, 301F / g, 424F / g, 339.1F / g, and 152F / g, respectively. With the introduction of Mn source, the specific capacitance of the prepared composite materials is higher than that of the material without adding manganese source. This is mainly due to the synergistic effect of heterojunction composite materials. With the increase of Mn content, the specific capacitance increases first and then decreases. The main reason for the increase first is the synergistic effect of the heterojunction of MnOx with VN and C. The main reason for the decrease in specific capacitance is that excessive manganese content will cause the dissolution of the electrolytic material and lead to a decrease in capacitance. Figure 4 The AC impedance spectra also show that the composite materials prepared in Examples 1 to 5 have smaller intrinsic impedance and charge transfer impedance than C / VN-700.

[0107] Figure 5 is the electrochemical performance of the samples at different temperatures. Figure 5 Figure a shows the cyclic voltammetry curves of the samples at different temperatures, which also show redox peaks. As the Mn content changes, the position of the redox peaks shifts slightly. In addition, Figure 5 Figure b shows that the charge and discharge curves have a small platform, which reflects the pseudocapacitive characteristics. Figure 5 In Figure c, at 0.5A / g, C / VN / MnO x -600-1, C / VN / MnO x -700-1C / VN / MnO x -800-1, C / VN / MnO x The specific capacitances of -900-1 are 12.3F / g, 424F / g, 210.2F / g and 163.2F / g respectively. When the temperature is low, the decomposition of C3N4 is incomplete, resulting in low conductivity and low specific capacitance of the generated material. As the temperature increases, the complete decomposition of C3N4 and the synergistic effect of the heterojunction of VN and MnOx with carbon materials lead to an increase in specific capacitance. When the temperature is raised to 800℃ or even 900℃, the decomposition of C3N4 intensifies, the carbon content decreases, and MnOx increases. x The content will increase, and the main electrode material VN will decrease, resulting in a downward trend in the specific capacitance of the overall composite material. Figure 6 The AC impedance spectrum also shows that the composite material C / VN / MnO x -700-1 and C / VN / MnO x -800-1 has smaller intrinsic impedance and charge transfer impedance.

[0108] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0109] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a carbon / vanadium nitride / manganese oxide composite material, characterized in that: The following steps are involved: The carbon nitride precursor is pyrolyzed once at 550°C to 600°C to obtain carbon nitride; acidifying the carbon nitride to obtain protonated carbon nitride; A manganese source is added to the vanadium pentoxide sol solution and stirred evenly, and then a hydrothermal reaction is carried out at 180° C. to 200° C. to obtain a manganese-vanadium complex; Under a protective atmosphere, the manganese-vanadium complex and protonated carbon nitride are subjected to secondary pyrolysis at 600° C. to 900° C. to obtain a carbon / vanadium nitride / manganese oxide complex.

2. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 1, characterized in that: The ratio of vanadium pentoxide to manganese source in the vanadium pentoxide sol solution is 2mmol:0.2g-4g.

3. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 1, characterized in that: The reaction time of the hydrothermal reaction is 1 h to 12 h.

4. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 1, characterized in that: The mass ratio of the manganese-vanadium complex to the protonated carbon nitride is 1:3-20.

5. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 1, characterized in that: The time of secondary pyrolysis is 1h to 4h.

6. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 1, characterized in that: The acidification treatment is to add carbon nitride to hydrochloric acid and react at room temperature for 2h to 5h.

7. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 6, characterized in that: The ratio of carbon nitride to hydrochloric acid is 1g:25-30ml.

8. The method for preparing a carbon / vanadium nitride / manganese oxide composite material according to claim 1, characterized in that: The time of one pyrolysis is 1h to 3h.

9. A carbon / vanadium nitride / manganese oxide composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon / vanadium nitride / manganese oxide composite material according to claim 9 in preparing electrode materials.